(untitled) (Boca Raton, 2009)
This book summarizes available fiber sources and how they can be incorporated into new food products to provide improved health benefits. It rigorously examines health claims, recent research, and contradictory data; covers fiber for weight and glycemic control, and intestinal regularity; and discusses how food producers can find fiber sources and include finer in their products. Critically examining current research and future directions, this resource blends coverage of the latest scientific information on the health benefits of fiber with information on how to formulate foods with higher concentrations of this vital nutrient
Keywords: Vai trò của chất xơ,Thực phẩm,Chề độ dinh dưỡng nhiều chất xơ,Fiber in human nutrition,Food,Dietary Fiber,Food, Fortified,Nutritive Value,Polysaccharides; Chất xơ,Fiber content,therapeutic use,therapeutic use